Komunikasi Pembangunan Islam dalam Pembentukan Karakter Positif Generasi Alpha di Era Digital - Salman; Azmiral Anwar; Sulaiman; M. Darul Amin Sitorus; Sabili Dahlan; Irma Yusriani Simamora (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to examine the role of Islamic development communication in the process of forming positive character for the Alpha generation in the digital era, as well as identifying strategies that can be implemented to maximize its impact in their daily lives. This method focuses on analyzing descriptive data in the form of a number of written words. The author uses a qualitative approach to analyze the focus of this research. The results of this research show that Islamic development communication has a very important role in shaping the positive character of the Alpha generation, especially in the digital era which is increasingly developing rapidly. In this context, Islamic development communication can be used as a strategic tool to instill positive values ​​in accordance with Islamic principles, such as morals, honesty, responsibility and empathy. By utilizing digital platforms that are popular among the Alpha generation, such as social media, applications and other digital content, Islamic messages that focus on character building can be conveyed in an interesting and relevant way. An effective communication approach, based on the principles of compassion, empowerment, and value-based education, can help direct the Alpha generation to face digital challenges wisely, and form individuals who have noble character and contribute positively to society. Keywords: Islamic Development Communication, Positive Character, Alpha Generation, Digital Era ABSTRAK. Penelitian ini bertujuan untuk mengkaji peran komunikasi pembangunan Islam dalam proses pembentukan karakter positif generasi Alpha di era digital, serta mengidentifikasi strategi yang dapat diterapkan untuk memaksimalkan dampaknya dalam kehidupan sehari-hari mereka. Metode ini menitikberatkan di analisis data deskriptif yang berupa sejumlah kata yang tertulis. Penulis menggunakan pendekatan kualitatif guna menganalisa fokus penelitian ini. Hasil penelitian ini memperlihatkan komunikasi pembangunan Islam memiliki peran yang sangat penting dalam membentuk karakter positif generasi Alpha, khususnya di era digital yang semakin berkembang pesat. Dalam konteks ini, komunikasi pembangunan Islam dapat dijadikan sebagai alat strategis untuk menanamkan nilai-nilai positif yang sesuai dengan prinsip-prinsip Islam, seperti akhlak, kejujuran, tanggung jawab, dan empati. Dengan memanfaatkan platform digital yang populer di kalangan generasi Alpha, seperti media sosial, aplikasi, dan konten digital lainnya, pesan-pesan Islam yang berfokus pada pembentukan karakter dapat disampaikan dengan cara yang menarik dan relevan. Pendekatan komunikasi yang efektif, berbasis pada prinsip kasih sayang, pemberdayaan, serta edukasi berbasis nilai, dapat membantu mengarahkan generasi Alpha untuk menghadapi tantangan digital dengan bijak, serta membentuk individu yang berakhlak mulia dan berkontribusi positif terhadap masyarakat.